Analysis of factors for determining suitable site for giant freshwater prawn (macrobrachium rosenbergii) farming through the local knowledge in Negeri Sembilan of Peninsular Malaysia - Ezekiel, Benjamin Bwadi; Mustafa, Firuza Begham; Ali, Mohammad Lokman; Bhassu, Subha (Universiti Putra Malaysia, 2018)
Prawn farming is one of the most important sectors emerging in the aquaculture industries in Malaysia which requires the consideration of the factors determining its spatial distribution. However, institutions charged with the responsibility of land suitability classification often neglect the incorporation of the local knowledge in their land use planning. The aim of the study was to identify the factors that determine the suitability of a site for giant freshwater prawn (Macrobrachium rosenbergii) farming in Negeri Sembilan of Peninsular Malaysia through the local knowledge. Data were collected from 64 prawn farmers and 10 fisheries officers in Negeri Sembilan using a questionnaire. Twelve factors were identified comprising water qualities (distance to sources of water, water temperature, water pH, distance to source of pollution), soil characteristics (land use type, slope, elevation, soil texture) and infrastructure facilities (distance to roads, distance to market, distance to electricity, distance to fry source). Pearson correlation and multiple regression statistics were applied to analyse the data. The correlation result revealed that giant freshwater prawn farming was greatly affected by water qualities with r(62) = 0.669, p=0.000 values, soil characteristics r(62) = 0.559, p = 0.000 values, and infrastructure factors r(62) = 0.566 with p = 0.000 values. The regression analysis indicated that the coefficient of determination R2 = 0.951, meaning that 95.1% of suitability is affected by the water quality, soil characteristics and the infrastructure facilities. Therefore, the determination of the factor for a suitable site for prawn farming can be achieved through the local knowledge.